The Legal Basis and Requirements for the Implementation of a Practical Training Profile - Piotrowski, Mariusz (Studia Oeconomica Posnaniensia, 2017)
In Poland in 1990 an institutional model of dual learning in higher education was introduced. The division into colleges and higher vocational schools was the division into colleges. From 2012, it created the legał basis for shaping academic profiles and the practical education of students. The implementation of a practical profile conclusion reąuires two types of contracts: a contract between the university and the entrepreneur and a contract between the trader and the student.